Factors Associated with Musculoskeletal Disorders Complaints of Medan Selayang Laundry Workers - Ginting, Johannes Bastira; Telaumbanua, Andika Syahputra; Siregar, Santy Deasy; Suci, Tri (Universitas Mandala Waluya, 2024)
Musculoskeletal Disorders (MSDs) complaints are often experienced by informal sector workers, including laundry workers, due to non-ergonomic work activities. This study evaluates the factors associated with MSD complaints among the Medan Selayang Sub-district laundry workers. The research design used a cross-sectional approach with 68 laundry workers as samples selected by purposive sampling. Data were collected using the Nordic Body Map questionnaire and analyzed using the Chi-Square test and multiple logistic regression to identify significant risk factors. The results showed that age (p=0.000), gender (p=0.045), tenure (p=0.002), and length of service (p=0.000) had a significant association with MSD complaints, while body mass index (BMI) showed no significant association (p=0.822). Multivariate analysis identified length of work as the most influential factor in MSD complaints with an Exp(B) value of 198.113. Recommendations include implementing occupational health and safety programs focused on high-risk workers, counseling on ergonomics, and setting policies related to work duration. These efforts are expected to reduce MSD complaints and improve the welfare of laundry workers.